The Level of Mental Health and its Relationship to Distance Education Among a Sample of Jordanians and Kuwaitis in Light of the Corona Pandemic - Alsaideh, Khawla Abdulkareem; Al-Shenikat, Feryal Abdel-Hadi; Shahadah, Rafat Shaheer (Journal of Ecohumanism, 2023)
The current study aimed to identify the level of mental health of students’ parents and university students in Jordan and Kuwait before and after the application of distance education and its relationship to some variables. The study sample consisted of (316) individuals, of whom (230) were females and (86) were males, and of them (239) students’ parents, (77) university students, (216) were from Jordan, and (100) were from Kuwait. And to achieve the objectives of the study, the Positive Mental Health Scale was used, after confirming its validity and reliability indications, and it was applied to the sample members in the two countries, Jordan and Kuwait. The data were analyzed statistically, where the results indicated that the level of mental health for the study sample before distance education was high, but after distance education, mental health decreased to a medium level, and it was also found that the health level of the Kuwaiti sample was higher than that of the Jordan sample, and that of males was higher than that of females, and statistically significant. Differences in mental health were found due to the number of children in schools, and the current study recommends conducting studies on the effect of simultaneous and asynchronous education on the mental health dimensions of students’ parents, and conducting qualitative studies to research the relationship of distance education to mental health in depth, the study also recommends that mental health authorities pay attention to the effects of the pandemic and the effects of distance education on parents, especially mothers.